Identification of peer effects using group size variation - Laurent Davezies; Xavier d'Haultfoeuille; Denis Fougère (Institute for the Study of Labor (IZA), 2006)
This paper considers the semiparametric identification of endogenous and exogenous peer effects based on group size variation. We show that Lee (2006)'s linear-in-means model is generically identified, even when all members of the group are not observed. While unnecessary in general, homoskedasticity may be required in special cases to recover all parameters. Extensions to asymmetric responses to peers and binary outcomes are also considered. Once more, most parameters are semiparametrically identified under weak conditions. However, recovering all of them requires more stringent assumptions. Eventually, we bring theoretical evidence that the model is more adapted to small groups
Keywords: 330; Gruppentheorie; Gruppentheorie; Soziale Gruppe; Soziale Beziehungen; Verhalten